The Effect of Renal Denervation on Plasma Adipokine Profile in Patients with Treatment Resistant Hypertension - Eikelis, Nina; Hering, Dagmara; Marusic, Petra; Duval, Jacqueline; Hammond, Louise J.; Walton, Antony S.; Lambert, Elisabeth A.; Esler, Murray D.; Lambert, Gavin W.; Schlaich, Markus P. (Frontiers in Physiology, 2017)
Abstract Background: We previously demonstrated the effectiveness of renal denervation (RDN) to lower blood pressure (BP) at least partially via the reduction of sympathetic stimulation to the kidney. A number of adipocyte-derived factors are implicated in BP control in obesity. Aim: The aim of this study was to examine whether RDN may have salutary effects on the adipokine profile in patients with resistant hypertension (RH). Methods: Fifty seven patients with RH undergoing RDN program have been included in this study (65% males, age 60.8±1.5 years, BMI 32.6±0.7 kg/m², mean±SEM). Throughout the study, the patients were on an average of 4.5±2.7 antihypertensive drugs. Automated seated office BP measurements and plasma concentrations of leptin, insulin, non-esterified fatty acids (NEFA), adiponectin and resistin were assessed at baseline and the 3 months after RDN. Results: There was a significant reduction in mean office systolic (168.75±2.57 vs 155.23±3.17 mmHg, p<0.001) and diastolic (90.68±2.31 vs 83.74±2.36 mmHg, p<0.001) BP 3 months after RDN. Body weight, plasma leptin and resistin levels and heart rate remained unchanged. Fasting insulin concentration significantly increased 3 months after the procedure (20.05±1.46 vs 29.70±2.51 uU/ml, p=0.002). There was a significant drop in circulating NEFA at follow up (1.01±0.07 vs 0.47±0.04 mEq/l, p<0.001). Adiponectin concentration was significantly higher after RDN (5654±800 vs 6644±967 ng/ml, p=0.024). Conclusions: This is the first study to demonstrate that RDN is associated with potentially beneficial effects on aspects of the adipokine profile. Increased adiponectin and reduced NEFA production may contribute to BP reduction via an effect on metabolic pathways.